Kopernikowska teoria pieniądza - Zajda, Józef (Wydział Prawa i Administracji UAM, 1973)
The theory of commodity money and the method of money analysis through its function formulated by Copernicus belong to the significant achievments of the history of economic thought. In the field of money theory there is so called Copernic Law, whose invention has been unjustly attributed to Gresham. The above mentioned Law can be formulated in short as follows: if there are two sorts of currency in circulation, having the same nominal value but not the same real (substantial) value, then the full-value coins (standart money) are driven out of circulation by undervalued money. Another Copernicus intellectual inventions in the domain of money theory are the following, 'still actual conceptions: a) unity of official and market price of currency metal constitutes the basic condition of functioning of metallic commodity money, b) transgression of the threshold of currency arbitrage (melting of currency into the pure metal) brings that unity down and therefore should be corrected by the state interventionism, c) creeping depreciation of currency originates usually negative and grave in results economic changes in the structure of prices. The Copernican views of money, especially the principle of periodicity of currency system reforms (every 25 years) and also that one concerning the subordination of currency to raison d'Etat are of great importance. To Copernicus the money has not been an object of its own, but it was the mean serving to an end. One of his statements said that the countries with full-value coins were prosperous in contradiistinctioin to those ones having had currency . . . and "good coin is not only advantegous to the state but also [...] to all classes of population while the bad money is disastrous".
Copernican Theory of Money